Prevalence and Pathological Lesions of Dermatophytosis in Cats (Felis catus) at the Animal Health Center in Cimahi: August-September 2023 - Fauziyah, Sri Nur Farah; Dewi, Intan Mauli Warma; Khairani, Shafia (Universitas Airlangga, 2025)
Dermatophytosis is a zoonotic fungal infection affecting the superficial skin layer. characterized by circular lesions commonly referred to as